2007
DOI: 10.1016/j.ejcts.2007.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Current surgical treatment of thoracic empyema in adults

Abstract: A review of the recent literature on treatment modalities of adult thoracic empyema was conducted in order to expose the controversies and verify where consensus exists. Critical reading filtered through clinical experience was the method followed. The roles of surgical drainage, lavage techniques, debridement via VATS, decortication, thoracoplasty and open window thoracostomy were considered using the Oxford Center of Evidence Based Medicine criteria. The roles of the different therapeutical modalities were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
185
1
33

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(224 citation statements)
references
References 74 publications
5
185
1
33
Order By: Relevance
“…Clinically it may provide better clues for the decision to perform the early surgical approach. The positive culture from the pleural space is assessed by different authors in 10-60% of patients (5,6,8,15,24,25,(28)(29)(30)(31)(32). Such a low percentage of positive cultures may represent an effective antibiotic treatment prior to sample collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically it may provide better clues for the decision to perform the early surgical approach. The positive culture from the pleural space is assessed by different authors in 10-60% of patients (5,6,8,15,24,25,(28)(29)(30)(31)(32). Such a low percentage of positive cultures may represent an effective antibiotic treatment prior to sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is a lack of data regarding the optimal timing of surgical intervention, so there is no consensus regarding this issue. Some recent studies identified that delayed referral to surgery or longer anamnesis lead to higher conversion rate and consequently increases morbidity and mortality (1,3,12,15,21,24,25,27). Chung and colleagues in their recent retrospective analysis of 120 cases of VATS empyemectomies stated that patients with the symptom duration of less than four weeks showed better early results compared to those with the symptom duration greater than four weeks (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As technology and medical science develops, in the last decades the video-assisted thoracic surgery (VATS) [8][9] has been demonstrated as an effective procedure in selected patients, allowing an optimal debridement of early organized pleural effusions. In the late phase of the pleural infectious process, when a thick pleural peel encases the lung, a pulmonary decortication is required and open approach is often needed [10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality and morbidity varies between 3% and 33%. [10][11][12][13] The most important issue to prevent morbidity or mortality is the prevention of disease progression and adequate aggressive treatment. ET carries many complications such as sepsis, respiratory failure, lung collapse, bronchopleural fistula (BPF), or gastropleural fistula.…”
mentioning
confidence: 99%